Effects of comprehensive group music therapy on affect and social functioning in patients with schizophrenia undergoing community-based rehabilitation: a preliminary study - Hong, Peikun; Xue, Chao; Lu, Junping; Wang, Mengying; Pan, Hongrun; Shao, Hua (Frontiers in Human Neuroscience, 2025)
Background and objectiveMost individuals with schizophrenia reside in the community, where they frequently encounter difficulties related to emotional problems and social functioning– critical areas of concern in the rehabilitation process. This study aims to investigate the effects of a comprehensive group music therapy intervention on the emotional state and social functioning of individuals with schizophrenia undergoing community rehabilitation.MethodsA total of 28 individuals with schizophrenia in community rehabilitation were randomly assigned to either the music intervention group (n = 14) or the control group (n = 14). The music intervention group participated in an 8-week comprehensive group music therapy intervention, while the control group continued with routine family life. The music therapy program was culturally adapted to the local community context, incorporating familiar regional music and dialect. The Positive and Negative Affect Schedule (PANAS) served as the primary outcome to assess affective changes, and the Social Disability Screening Schedule (SDSS) served as the secondary outcome to evaluate social functioning. Both measures were administered pre- and post-intervention. In addition, some participants in the intervention group completed semi-structured interviews to explore changes in social functioning and affect.ResultsFollowing the intervention, the music therapy group showed significant improvements in positive affect, social activities and self-care, as measured by the PANAS and SDSS, respectively. In contrast, no significant pre-post changes were observed in the control group. Semi-structured interviews further supported these findings, with participants in the intervention group reporting enhanced emotional state and improved social functioning.ConclusionComprehensive group music therapy appears to be an effective intervention for improving emotional states and social functioning in individuals with schizophrenia engaged in community rehabilitation. This culturally adapted intervention model demonstrates its potential for broader application.